Citrullinated Inhibitor of DNA Binding 1 Is a Novel Autoantigen in Rheumatoid Arthritis. Issue 8 (21st June 2019) - Ohara, Ray A.; Edhayan, Gautam; Rasmussen, Stephanie M.; Isozaki, Takeo; Remmer, Henriette A.; Lanigan, Thomas M.; Campbell, Phillip L.; Urquhart, Andrew G.; Lawton, Jeffrey N.; Chung, Kevin C.; Fox, David A.; Ruth, Jeffrey H.
Abstract : Objective: To explore the intrinsic role of inhibitor of DNA binding 1 (ID‐1) in rheumatoid arthritis (RA) fibroblast‐like synoviocytes (FLS) and to investigate whether ID‐1 is citrullinated and autoantigenic in RA. Methods: RA patient serum ID‐1 levels were measured before and after infliximab treatment. RA FLS were transfected with a clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated protein 9 construct targeting ID‐1 to examine the effects of ID‐1 deletion. RA synovial fluid (SF) and homogenized synovial tissue (ST) were immunoprecipitated for ID‐1 and measured for citrullinated residues using an enzyme‐linked immunosorbent assay and Western blotting. Liquid chromatography tandem mass spectrometry (LC‐MS/MS) was performed on in vitro–citrullinated recombinant human ID‐1 (cit–ID‐1) to localize the sites of citrullination. Normal and RA sera and SF were analyzed by immunodot blotting for anti–citrullinated protein antibodies (ACPAs) to cit–ID‐1. Results: RA patient serum ID‐1 levels positively correlated with several disease parameters and were reduced after infliximab treatment. RA FLS displayed reduced growth and a robust increase in interleukin‐6 (IL‐6) and IL‐8 production upon deletion of ID‐1. ID‐1 immunodepletion significantly reduced the levels of citrullinated residues in RA SF, and citrullinated ID‐1 was detected in homogenized RA ST (n = 5 samples; P < 0.05). Immunodot blot analyses revealed ACPAs to cit–ID‐1 but not to native ID‐1, in RA peripheral blood (PB) sera (n = 30 samples; P < 0.001) and SF (n = 18 samples; P < 0.05) but not in normal PB sera. Following analyses of LC‐MS/MS results for citrullination sites and corresponding reactivity in immunodot assays, we determined the critical arginines in ID‐1 for autoantigenicity: R33, R52, and R121. Conclusion: Novel roles of ID‐1 in RA include regulation of FLS proliferation and cytokine secretion as well as autoantigenicity following citrullination.